Blindness and visual impairment: quality of life and accessibility in the city of Turin - Alessia Nuzzi; Alice Becco; Andrea Boschiroli; Andrea Coletto; Raffaele Nuzzi (Frontiers in Medicine, 2024)
PurposeDespite the increase in socio-health conditions and, in general, the focus on health worldwide, many diseases still adversely affect the quality of life (QoL), including those causing vision loss. The main purpose of this study was to evaluate the QoL of people with visual impairments through a questionnaire and identify issues concerning everyday life in the urban and extra-urban areas of Turin.Patients and methodsA personalized questionnaire including 25 questions was distributed to 100 enrolled patients. It was designed by integrating the most widely used questionnaires related to the QoL of people with visual impairment with questions concerning the city of Turin. The inclusion criteria were any degree of visual impairment (from mild defect to complete blindness), according to Law n. 138/2001 classification. The exclusion criteria were mental disability and residence in care homes. Finally, statistical analysis was performed. Pearson’s Chi-Square test was used to evaluate the strength of the association between two qualitative variables in different sections of the questionnaire. The results were classified as statistically significant with a p-value of ≤0.05 or borderline (0.05 < p-value<0.10).ResultsBased on responses to question 7 (Q7), 67% of selected patients stated that sight markedly influences their QoL. Moreover, 49% of patients responding to question 12 considered themselves almost completely dependent on other people regarding mobility and movement in and around Turin. In total, 57% used public transport (Q13); however, 50% of them found it challenging to access (Q14). Personal aids (e.g., white cane and magnifying glasses) were adopted only by 51% (Q15), and 63% of patients responding to question 18 suggested a refinement of urban aids (e.g., road signs). Of the 53 patients, 30 patients (56.6%) considered Turin a livable city for visually impaired people (Q19); however, 44 patients (84.6%) reported no significant improvements in Turin’s urban logistics during the last 5 years and highlighted the urgent need to improve urban aids (Q21). Furthermore, the statistical associations studied showed that the loss of vision plays a significant role in influencing the perception of one’s QoL (association of questions 7 and 8, X2 = 112.119, Cramer’s V = 0.548, p-value <0.001). In addition, it is more difficult for visually impaired patients living outside the city to move outdoors (Chi-Square = 10.637, Cramer’s V = 0.326, p − 245 value = 0.031) and to cross the street (Chi-Square = 14.102, Cramer’s V = 0.376, p-250 value = 0.007). Finally, those who feel independent perceive their lives to be more fulfilling (Chi-Square = 268, X2 = 37.433; Cramer’s V = 0.306, p value = 0.002).ConclusionOur study showed how vision loss plays a remarkable role in influencing the perception of one’s QoL. Furthermore, it highlighted how the implementation of mobility and the use of personal aids for living in a city, such as Turin, were associated with a better perception of QoL by visually impaired patients. However, it is necessary to improve urban technological development according to the needs of people with visual disability.